OPTIMIZATION OF PRODUCTIVITY OF RICE BEAN PLANTS (Vigna angularis L.) BY UTILIZING BIOCHAR AND GOAT MANURE - Pareira, Magdalena Sunarty; Lau, Fansiska Xaveria; Naikofi, Kristina Irnasari (Universitas Veteran Bangun Nusantara, 2025)
This study aims to determine the effect of the best dosage of biochar and goat manure on the growth and yield of rice beans (Vigna umbellata.) and to determine the interaction between the administration of biochar and goat manure on the growth and yield of rice beans (Vigna umbellata.). This study used a two-factorial completely randomized design consisting of 2 factors, namely: the first factor is biochar consisting of 3 levels: biochar 5 tons/ha, biochar 10 tons/ha, and biochar 15 tons/ha. The second factor is goat manure consisting of 3 levels, namely: goat manure 5 tons/ha, goat manure 10 tons/ha, and goat manure 15 tons/ha. Based on the treatment levels used, 9 combinations were obtained which were repeated 5 times so that there were 45 experimental units. The results of the variance analysis showed a significant interaction between the treatment of biochar and goat manure on the length of pods and the number of seeds per plant, but had no effect on seed weight. The best combination was found at a dose of 15 tons/ha of biochar and 15 tons/ha of goat manure, which produced the highest pod length of 11.70 cm. and the number of seeds (31.40 seeds). These results indicate that the synergy between the two treatments can significantly increase plant yields compared to single treatments. This research demonstrates the value of treatment combinations to increase plant productivity, as well as the need for further exploration for more optimal doses and combinations. Keywords: Biochar, Adzuki Bean, Goat Manure.